How Corporate Political Strategies Are Related to Cost of Debt? - Amanat, Aamir; Hunjra, Ahmed Imran; Ahmed, Farhan (The Indonesian Capital Market Review, 2020)
There are many factors, which play a vital role in the financing decisions of firms, and one of the important factors is corporate political strategies. This study examines the impact of corporate political strategies on the cost of debt of non-financial firms listed in the Pakistan Stock Exchange (PSX). Corporate political strategies are measured through political connections. We use panel data of 250 firms from 2001 to 2018. Panel regression is applied to analyze the results. This study finds corporate political strategies negatively affect the cost of debt. This study provides useful policy implications for corporate stakeholders to know the importance of political connections while making the financing decision.